Dimorfismo sexual em Cnemidophorus lacertoides (Squamata, Teiidae) do sul da América do Sul - Feltrim, Aline Costa (Phyllomedusa: Journal of Herpetology, 2002)
Twenty-five adult males and 22 adult females from different populations along the distribution range of Cnemidophorus lacertoides were compared using color and six morphometric variables. Sexual differences in snout-vent length were tested by analysis of variance. Sexual differences in tail length, tail width, head length, head width, and head height were tested by analysis of covariance using snout-vent length as the covariate. All measurements but snout-vent length were significantly different between sexes, males being larger than females. Adult males also have a green coloration on the lateral sides of the body not seen in females.